Audio-Visual Aids in English Foreign Language (EFL) Teaching A Multimodal Discourse Analysis - Silvia Umrotun Nafiah (Universitas Stikubank (UNISBANK) Semarang, 2023)
Through a multimodal discourse analysis, this study investigates the use of audio-visual aids in English Foreign Language (EFL) education. The study looks into the multimodal characteristics of audio-visual aids, their interaction, and their impact on language acquisition. The study employs a qualitative research methodology and a variety of data collection methods, such as classroom observations, video recordings, and interviews with EFL teachers. The data is examined using multimodal discourse analysis approaches, with a focus on the incorporation of visuals, audio, gestures, and interactive aspects. The findings highlight the various multimodal characteristics of audio-visual aids and their importance in providing a rich and engaging learning environment. The study emphasizes the interactive aspect of audio-visual aids and their potential to improve language learning experiences by connecting language to real-life circumstances, adapting to different learning styles, and encouraging active engagement. There is also discussion of pedagogical strategies for effective integration and advice for dealing with issues related with audio-visual aids in EFL instruction. This study adds to the current body of knowledge on audio-visual aids in EFL instruction by giving empirical evidence of its multimodal nature and impact on language learning. The findings provide educators with insights into how to best use audio-visual aids and encourage effective language learning in the EFL classroom.